A new in vitro model of polymyositis reveals CD8+ T cell invasion into muscle cells and its cytotoxic role. (30th June 2019) - Kamiya, Mari; Mizoguchi, Fumitaka; Takamura, Akito; Kimura, Naoki; Kawahata, Kimito; Kohsaka, Hitoshi
Abstract: Objectives: The hallmark histopathology of PM is the presence of CD8 + T cells in the non-necrotic muscle cells. The aim of this study was to clarify the pathological significance of CD8 + T cells in muscle cells. Methods: C2C12 cells were transduced retrovirally with the genes encoding MHC class I (H2K b ) and SIINFEKL peptide derived from ovalbumin (OVA), and then differentiated to myotubes (H2K b OVA-myotubes). H2K b OVA-myotubes were co-cultured with OT-I CD8 + T cells derived from OVA-specific class I restricted T cell receptor transgenic mice as an in vitro model of PM to examine whether the CD8 + T cells invade into the myotubes and if the myotubes with the invasion are more prone to die than those without. Muscle biopsy samples from patients with PM were examined for the presence of CD8 + T cells in muscle cells. The clinical profiles were compared between the patients with and without CD8 + T cells in muscle cells. Results: Analysis of the in vitro model of PM with confocal microscopy demonstrated the invasion of OT-I CD8 + T cells into H2K b OVA-myotubes. Transmission electron microscopic analysis revealed an electron-lucent area between the invaded CD8 + T cell and the cytoplasm of H2K b OVA-myotubes. The myotubes invaded with OT-I CD8 + T cells died earlier than the uninvaded myotubes. The level of serum creatinine kinase was higher in patients with CD8 + T cells in muscle cells than those without these cells. Conclusion: CD8 + T cells invade into muscle cells and contribute to muscle injury in PM. Our in vitro model of PM is useful to examine the mechanisms underlying muscle injury induced by CD8 + T cells.